Biosorption of Congo Red Dye from Aqueous Solution Using Adsorbent Prepared from Vangueria infausta Fruit Pericarp - Aisha Kitemangu; Maheswara Rao Vegi; Nyemaga Masanje Malima (Adsorption Science & Technology)
The adsorption efficiency of acid-treated Vangueria infausta fruit pericarp (VIFP) biosorbent to uptake Congo red (CR) dye was investigated through batch experiments. Optimum conditions for the adsorption process were determined by varying the solution pH, biosorbent dosage, contact time, initial concentration of CR dye, and temperature. Results revealed that the data fits well with the Langmuir isotherm model, demonstrating the monolayer coverage of the CR dye molecule on the surface of the VIFP biosorbent. The higher value of correlation coefficient, R2 for pseudo-second-order (0.9997) compared to R2 of pseudo-first-order (0.9605) suggests that the pseudo-second-order kinetic model is an ideal fit in describing the kinetics of CR dye adsorption by VIFP biosorbent. The positive value of ΔH° (41.42 kJ/mol) and ΔS° (158.32 J/mol.K) depicts the endothermic nature and spontaneity of the biosorption of CR dye by VIFP. The values of ΔG° obtained were negative, showing that the adsorption is thermodynamically favourable. Therefore, the acid-treated adsorbent from Vangueria infausta can efficiently be used in the removal of CR dye from aqueous solution.